Realization of Hubbul Ilmii Book to Improve Basic Reading Skills in Lower Grade Students - Eftiana Dwi Zhahrani; Afiful Ikhwan; Devid Dwi Erwahyudin (Yayasan Letiges Konsultan Sosial, 2025)
The purpose of this study is to analyze more deeply about the effectiveness of the realization of the Hubbul Ilmii book in improving basic reading skills in lower grade students. These namely students are at the elementary school level from grade 1 to grade 3. This study was conducted at the Griya Qur'an Al Inayah Pulung Ponorogo Foundation. The method used is a qualitative approach to the case study type, data collection used with semi-structured interviews, non-participant observation, and documentation. The primary data sources in this study were the female teachers who accompanied the study, the students, and the head of the foundation. The data analysis technique used the Miles and Huberman model, namely data collection, reduction, data presentation and drawing conclusions. Data validity was carried out by triangulation, which includes technical triangulation, data source triangulation, and time triangulation. The results of this study were found to be obstacles to students' reading difficulties in elementary schools, namely difficulty in distinguishing the same letter shapes. The realization of learning media used from the Hubbul Ilmii book can facilitate students' early reading skills with the introduction of vowels and syllables in just 36 meetings divided into three levels, increasing children's reading skills at each meeting. The use of Hubbul Ilmii book media and the method of cutting, coloring and sticking letters can have a positive impact on students, especially in terms of learning basic reading. Students become more focused, do not feel bored and can be involved in direct learning. In addition, students also find it easy to accept learning, making it easier for teachers to transfer knowledge to students.